Fitness and fur colouration: Testing the camouflage and thermoregulation hypotheses in an Arctic mammal. Issue 5 (17th March 2021) - Di Bernardi, Cecilia; Thierry, Anne‐Mathilde; Eide, Nina E.; Bowler, Diana E.; Rød‐Eriksen, Lars; Blumentrath, Stefan; Tietgen, Lukas; Sandercock, Brett K.; Flagstad, Øystein; Landa, Arild
Abstract: Selection for crypsis has been recognized as an important ecological driver of animal colouration, whereas the relative importance of thermoregulation is more contentious with mixed empirical support. A potential thermal advantage of darker individuals has been observed in a wide range of animal species. Arctic animals that exhibit colour polymorphisms and undergo seasonal colour moults are interesting study subjects for testing the two alternative hypotheses: demographic performance of different colour morphs might be differentially affected by snow cover with a cryptic advantage for lighter morphs, or conversely by winter temperature with a thermal advantage for darker morphs. In this study, we explored whether camouflage and thermoregulation might explain differences in reproduction and survival between the white and blue colour morphs of the Arctic fox Vulpes lagopus under natural conditions. Juvenile and adult survival, breeding propensity and litter size were measured for 798 captive‐bred and released or wild‐born Arctic foxes monitored during an 11‐year period (2007–2017) in two subpopulations in south‐central Norway. We investigated the proportion of the two colour morphs and compared their demographic performance in relation to spatial variation in duration of snow cover, onset of snow season and winter temperatures. After population re‐establishment, a higher proportion of blue individuals was observed among wild‐born Arctic foxes compared to the proportion of blue foxes released from the captive population. Our field study provides the first evidence for an effect of colour morph on the reproductive performance of Arctic foxes under natural conditions, with a higher breeding propensity of the blue morph compared to the white one. Performance of the two colour morphs was not differentially affected by the climatic variables, except for juvenile survival. Blue morph juveniles showed a tendency for higher survival under colder winter temperatures but lower survival under warmer temperatures compared to white morph juveniles. Overall, our findings do not consistently support predictions of the camouflage or the thermoregulation hypotheses . The higher success of blue foxes suggests an advantage of the dark morph not directly related to disruptive selection by crypsis or thermoregulation. Our results rather point to physiological adaptations and behavioural traits not necessarily connected to thermoregulation, such as stress response, immune function, sexual behaviour and aggressiveness. Our findings highlight the need to explore the potential role of genetic linkage or pleiotropy in influencing the fitness of white and blue Arctic foxes as well as other species with colour polymorphisms. Abstract : Crypsis might explain fur coloration in the Arctic, but thermoregulation may also play a role. The authors studied 798 Arctic foxes and compared the fitness of white and blue morphs. The authors document for the first time a higher mean fitness of the blue morph, possibly associated with physiological or behavioural traits.